Using Pragmatic Grounded Theory in the evaluation of public policies - Krupnik, Seweryn; Turek, Konrad (Journal of Public Governance, 2014)
The article presents the methodology of pragmatic grounded theory as a research strategy for the evaluation of public policies, basing on a reconsideration of the links between the pragmatism of Charles S. Peirce, grounded theory and the methodology of evaluation. The main characteristics of the approach are illustrated with an example of an empirical study of the evaluation of investment subsidies for small and medium enterprises in Poland. We summarise and discuss the usefulness of Pragmatic Grounded Theory for public policy studies and its limitations, as well as the links to other methodological approaches in the social sciences.